Singlet Fission Driven by Anisotropic Vibronic Coupling in Single-Crystalline Pentacene - Deng, Gang-Hua; Qian, Yuqin; Li, Xia; Zhang, Tong; Jiang, Wei; Harutyunyan, Avetik R; Chen, Gugang; Chen, Hanning; Rao, Yi (The journal of physical chemistry letters, 2021)
Vibronic coupling is believed to play an important role in siglet fission, wherein a photoexcited singlet exciton is converted into two triplet excitons. In the present study, we examine the role of vibronic coupling in singlet fission using polarized transient absorption microscopy and simulations on single-crystalline pentacene. It was found that singlet fission in pentacene is greatly facilitated by the vibrational coherence of a 35.0 cm phonon, where anisotropic coherence persists extensively for a few picoseconds. This coherence-preserving phonon that drives the anisotropic singlet fission is made possible by a unique cross-axial charge-transfer intermediate state. In the same fashion, this phonon was also found to predominantly drive the quantum decohence of a correlated triplet pair to form a decoupled triplet dimer. Moreover, our transient kinetic experimental data illustrates notable directional anisotropicity of the singlet fission rate in single-crystalline pentacene.